Agreement level of preoperative histology with post-surgical histology in atypical hyperplasia and endometrial cancer patients - Dalal, Venus; Asal, Raghda; Bharti, Shipra; Kumar, Vanitha; Toshyan, Varnit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometrial cancer significantly contributes to gynecological cancers. The aim of the study was to assess the concordance between the preoperative endometrial biopsy and histology of hysterectomy specimens in patients surgically treated for endometrial hyperplasia and endometrial cancer. Concurrent malignancy was also assessed in cases of endometrial hyperplasia with atypia. Methods: This study is a retrospective analysis of patients surgically treated for atypical hyperplasia (47 patients) and cancer (210 patients) at HHFT from January 2014 to March 2020. The preoperative histology was compared to the histological findings of hysterectomy. In cases of endometrial cancer, its histological type and grade were also assessed. Results: In the endometrial cancer group, the majority were endometrioid adenocarcinoma (204 patients) and only 6 had a non-endometrioid type. In the endometrioid and non-endometrioid group, preoperative diagnosis was confirmed in 88.7% and 100% patients respectively in postoperative specimens. Tumor grade was reported in 193 patients. The present study shows the highest accuracy in grade 3 patients (88%) followed by grade 1 (82.8%) and grade 2 (62.5%). Out of these 47 patients who underwent surgical management for atypical hyperplasia, preoperative diagnosis was confirmed in 46.8% (22 patients). Importantly, concurrent endometrial cancer in hysterectomy specimens was found in 34% patients in atypical hyperplasia group. Conclusions: High level of concordance was noticed in histology and grade in endometrial cancer patients. Only half of the patients in atypical hyperplasia group showed concordance as one-third of patients were found to have concurrent malignancy.